The influence of access to financial services and effective financial management practices on SME success in South Africa - Sisusa, Ubenathi (Rhodes University, Faculty of Commerce, Department of Management)
The success rate of small and medium enterprises (SMEs) in South Africa is still low due to the majority failing in their early stages of initiation. The main reasons why SMEs fail can be ascribed to their lack of access to financial services and effective financial management practices. Access to financial services refers to the ability of SMEs to obtain financial products and services from formal financial institutions at affordable prices, while effective financial management practices refer to the adoption of cash and credit management practices to efficiently manage finances within the SMEs. This study investigated the influence of access to financial services and effective financial management practices on SME success in South Africa. Access to financial services was measured by SMEs' access to transactional bank accounts, savings accounts, credit facilities, and insurance products. Effective financial management practices were measured according to their cash and credit management practices. Lastly, SME success was measured as SMEs operating for over five years, reporting growth according to the owner's perception, and earning annual profits of R15 000 and above. This study applied the quantitative research design to investigate the influence of access to financial services and effective financial management practices on SME success in South Africa. The study used existing data collected by Ipsos for the FinMark Trust FinScope South Africa MSME 2020 with a sample of 4 897 respondents. The study used secondary data to investigate the independent variables, namely access to financial services and effective financial management practices, on the dependent variable, SME success. Pearson's correlation coefficient and the multiple regression analysis were used to test the hypotheses of the study. The results showed that these SMEs were mostly from the Gauteng Province (40%), the majority had between 11 and 50 employees (76%), and the owner was the manager (73%). Pearson's correlation coefficient results showed a significant positive correlation between access to financial services and SME success. It also showed a significant positive correlation between effective financial management practices and SME success. Furthermore, this study's multiple regression analysis showed that access to financial services and effective financial management practices significantly influence SME success. Thus, SMEs with access to financial services (transactional bank accounts, savings accounts, credit facilities, and insurance products) and adopting effective financial management practices such as cash and credit management are likely to succeed. This study emphasises the importance of access to financial services and effective financial management practices on SMEs' success. Therefore, it is recommended that to enhance SME success, SMEs need to open transactional bank accounts as soon as they start operating to ensure that they build favourable profiles with the financial institutions to gain access to other financial services such as credit facilities and insurance products. Furthermore, in terms of effective financial management practices, SMEs need to adopt the relevant cash and credit management practices, ensuring that they can meet the financial institutions' requirements, subsequently enabling them to access financial services. Lastly, this study recommends that financial institutions offer relevant and affordable financial products and services to SMEs to ensure they can access more financial services. This study contributes to SMEs and formal financial institutions in South Africa by identifying the factors that influence SME success, the measures that SME owners can put in place for the SMEs to be successful, the role that formal financial institutions play in enabling SMEs' success, and the changes they can implement to aid SMEs to access financial services at affordable costs.
Keywords: Financial services industry -- South Africa; Democratization of finance; Small business Finance; Small and medium enterprises; Resource-based view